Kewenangan Otonomi Khusus Pemerintah Aceh dalam Pembangunan dan Peningkatan Kesejahteraan Rakyat - ardiyansyah, Amzar; Nazaruddin, Nazaruddin (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2024)
Purpose: This study aims to see the authority of the Government of Aceh towards the development and welfare of the people in Aceh Province through a special autonomy system, special authority as stipulated in Law Number 11 of 2006 concerning the Government of Aceh, because the authority to manage and administer government is an executive institution. Methodology/approach: The research method is juridical normative using secondary data collecting secondary, primary and tertiary materials, the data obtained is carried out qualitative analysis that emphasizes deductive and inductive. Results/findings: The results of the study show that the Government of Aceh has not maximized its authority in implementing the government and using the Special Autonomy Fund for development and community welfare, most of the Special Autonomy Fund is not right on target for the public interest, efforts made by the Government of Aceh and the Aceh People's Representative Council in the future formulate and compile the Aceh Revenue and Expenditure Budget according to needs and interests community. Limitations: This study does not include a table of programs and financial conditions of special autonomy because this research is normative so it does not conduct field research to obtain research data. Contribution: The Government of Aceh to focus on carrying out development not only on physical but non-physical as well, is needed to bring investors from within and outside the country, and place competent people in their fields in the Aceh Government Work Unit, as well as the role of the Aceh People's Representative Council to conduct extra supervision to the Government of Aceh as a user of the budget and organizer of laws and regulations in the Province Aceh.